Cool colour impact towards occupant’s thermal comfort and sensation / Zaim Ahnaf Abd Rahim, Azizah Md Ajis and Zulkarnain Hazim - Abd Rahim, Zaim Ahnaf; Md Ajis, Azizah; Hazim, Zulkarnain (2022)
Colour being the characteristic of any indoor environment was commonly used for its beautification and triggering human behaviour, emotion and changing perceived dimension. However, the thermal impact of colour has rarely been used to its fullest benefits in the interior. This study aims to identify cool colours that influence occupants’ thermal comfort and sensation. Content analysis and colour preference surveys have been carried out. Analysis of past studies found that cool colour consists of blue, blue-green, green, purple and purple-blue hue where cool colour has been identified to make people feel cooler in a warm environment. 3 sample colours with different ratios of brightness and saturation had been selected for blue-green, green, purple and purple-blue hues from the Munsell colour chart to be used in the colour preference survey. 390 participants from different ages, gender and race had volunteered in the survey. The most preferred colour for each hue was Summer space (green), Neptune Jewel (blue-green), Bangor blue (purple-blue) and Proudly purple (purple). Recent studies showed that cool colours manipulate people to feel cooler. However, the colour sample use was too general. Therefore, the result from this study helps in providing specific cool colour that soothes the eye of occupants and thermally comforting for sustainable interior design purposes to achieve human health and well-being in the built environment.